Dynamic multimapping composite chaotic sequence generator algorithm - Liu, Fang; Feng, Yongxin (International journal of electronics and communications, 2019)
In this study, a dynamic multimapping composite (DMMC) chaotic sequence algorithm is proposed to overcome the drawback with respect to the availability of only a limited number of sequences and fixed mechanism in the direct sequence spread spectrum communication, based on the improved Logistic, Chebyshev and Kent mappings. The control parameters are used to determine the odd mapping and even mapping, and the fractal function is established. Then, the selection function and optimal function are established by alternatively driving the odd mapping and even mapping, and the optimal sequence is generated. The test results with respect to sensitivity, balance, run and correlation indicate that the sequence generated by the DMMC algorithm demonstrates obvious advantages and flexibility.